Arabic automatic continuous speech recognition systems - Abushariah, Mohammad A. M.; Zainuddin, Roziati; Alqudah, Assal Ali Mustafa; Khalifa, Othman Omran (IIUM Press, 2011)
MSA is the current formal linguistic standard of Arabic language, which is widely taught in schools and universities, and often used in the office and the media. MSA is also considered as the only acceptable form of Arabic language for all native speakers [I]. As recently, the research community has witnessed an improvement in the performance of ASR systems, there is an increasingly widespread use of this technology for several languages of the world. Similarly, research interests have grown significantly in the past few years for Arabic ASR research. It is noticed that Arabic ASR research is not only conducted and investigated by researchers in the Arab world, but also by many others located in different parts of the \vorld especially the western countries.